Legal instruments for sustainable soil management in Africa - Yahyah, Hadijah; Ginzky, Harald 1964-; Kasimbazi, Emmanuel; Kibugi, Robert; Ruppel, Oliver C. 1969- (International yearbook of soil law and policy. Regional perspectives, 2020)
This book presents an important discussion on future options for sustainable soil management in Africa from various perspectives, including national soil protection regulations, the role of tenure rights, the work of relevant international institutions such as the UNCCD and FAO, and regional and international cooperation. This first volume of the new subseries Regional Perspectives to the International Yearbook of Soil Law and Policy includes contributions by African and international experts alike. Given the range of key topics covered, the book offers an indispensable tool for all academics, legislators and policymakers working in this field. The "International Yearbook of Soil Law and Policy - Regional Perspectives" series discusses central questions in law and politics that concern the protection and sustainable management of soil and land in different regions of the world